Fall Armyworm (Spodoptera frugiperda) in Maize: Current Status and Collaborative Efforts for its Management in Nepal - Sah, L.P.; Lamichhaney, D.; KC, H.B.; Acharya, M.C.; Humagain, S.P.; Bhandari, G.; Maniappan, R. (Journal of the Plant Protection Society, 2020)
Abstract available with the full text.